Traumatic Submacular Hemorrhage with Macular Hole Repaired by Pneumatic Displacement and Intravitreal t-PA Injection - Amy A. Mehta; Jay Berdia; Lilly H. Wagner; Irene Choi; Brandon B. Johnson (Case Reports in Ophthalmological Medicine)
This paper presents a case demonstrating repair of traumatic macular hole and submacular hemorrhage with intravitreal gas tamponade and t-PA in an office setting.